Peranan Konseling Multibudaya Terhadap Penanganan Radikal Pada Remaja - Afifa, Nur (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
Indonesia, as a multicultural country with diverse ethnicities, religions, teachings and understandings, has the opportunity to open up opportunities for various understandings to influence it. The world of education is one of the potential targets for spreading the seeds of radicalism. Radicalism tends to ignore aspects of diversity (uniformity) and eliminate diversity (plurality). The psychological condition of adolescents is a period that is vulnerable and sensitive to environmental influences. During this period, adolescence is synonymous with the period of searching for identity and the desire to solidify one's philosophy of life. Guidance and counseling services are one of the services in the world of education that is very strategic in tackling the spread of the seeds of radicalism. Counseling services through the multicultural concept are considered very necessary in forming young people who are able to respect each other in every difference. Therefore, this research aims to show that multicultural counseling is one way to foster civilized attitudes in students so that they do not fall into a wrong understanding of differences.Keywords: Multicultural, Counseling, Handling Radicalism, Adolescents